Analysis of antibiotic residues in milk from smallholder farms in Kenya - Ahlberg, Sara H.; Korhonen, H.; Lindfors, E.; Kang'ethe, Erastus K. (2016)
The aim of this study was to determine the occurrence of antibiotic residues in Kenyan smallholder farm milk using screening tests, and to identify the antibiotic residue group. A total of 480 milk samples were analyzed. All samples were analyzed with the Delvotest® screening test. A Hundred and fourteen (24%) samples were positive, 71 (15%) unclear and 295 (61%) negative. Sixty-two samples were further tested with the group specific Trisensor test. Twenty four percent (15/62) were positive. This indicated that by estimation, 9% of all the 480 samples have been positive with the Trisensor test and 5% would have contained beta-lactams, 2.5 % sulfonamides and 0.6 % tetracyclines. Samples with a positive Trisensor test results were further analyzed with HPLC but no antibiotics could be identified. Seventy six percent of the Delvotest® positive samples were negative in Trisensor test. Microbiological inhibitor methods are demanding for the sample conditions and were found not to be best suited to the conditions encountered in smallholder farms in Kenya. The results indicate that antibiotic residues are found in milk produced on small scale farms in Kenya and suggest that training is needed on the use of veterinary drugs.